Analysis of Students' Critical Thinking Skills Based on Prior Knowledge Mathematics - Kania, Nia; Fitriani, Cut; Bonyah, Ebenezer (EDUPEDIA Publisher, 2023)
The development of critical thinking skills has emerged as a global concern in a variety of fields, including education. The purpose of this research is to shed light on the connection that exists between one's prior knowledge and the mathematical critical thinking skills that are acquired through the use of quantitative methods. Collecting data through the use of mathematical instruments, mathematical critical thinking tests, and daily test data for the prerequisite material based on the average student's performance. High school students in the eleventh grade made up the study's sample population. The findings of the research indicate that there is a positive connection between mathematical background knowledge and critical thinking abilities in that subject area. It is possible to draw the conclusion that the material that serves as initial knowledge and is therefore a prerequisite needs to be studied extensively in order to have broad insight that contributes to the success of learning the subsequent material. In spite of this, the researchers discovered that the number of students who fell into the high and medium categories of critical thinking skills was lower when compared to the number of students who fell into the second category when it came to their initial mathematical abilities. In other words, there has been a rise in the proportion of students who score poorly on tests of their ability to engage in critical thinking. These additional aspects should be sought out and incorporated as research fodder in subsequent studies.